PLANNING FOR ESTABLISHING STEM EDUCATION DEPARTMENT WITHIN FACULTY OF EDUCATION - AIN SHAMS UNIVERSITY AN INTERDISCIPLINARY MODEL - Khadri, Hanaa Ouda (European Scientific Journal, ESJ, 2014)
The goal of the Egyptian Ministry of Education is to establish twenty-seven STEM schools over the course of five years . Teachers lack adequate support, including appropriate professional development as well as interesting and intriguing curricula. There is a real problem faces the Ministry of Education, that is the qualified STEM education teachers, in the main time there is no an academic department of [STEM] Education in the Egyptian universities preparing STEM education teachers , provide appropriate professional development and expand and enhance STEM Education in Egypt in significant ways. The objective of this Study is to propose a plan to Establish a Department [STEM] Education within the Faculty of Education - Ain Shams University.